IMPLEMENTASI REKRUTMEN GURU DISD TA’MIRUL ISLAM SURAKARTA (KAJIAN MANAJEMEN SUMBER DAYA MANUSIA DI SD ISLAM) - Rohmatun Lukluk Isnaini (Jurnal Pendidikan Agama Islam, 2015)
The main objective in the recruitment process in schools is getting human resources or educators (teacher) is appropriate for a particular position so that the person is able to work optimally and can survive in school for a long time. Implementation of recruitment is a very important task, crucial and requires a great responsibility. This is because the quality of human resources that will be used schools rely heavily on recruitment and selection procedures were carried out. Based on interviews and observations made, it can be analyzed that the implementation of teacher recruitment aims to get teachers who are professional and have the best qualifications. Recruitment of new teachers is not held every year since in accordance with the needs of the school if there are vacant positions then held recruiting new teachers to fill positions corresponding field. Before conducting the necessary preparation for the recruitment of new teachers, new teacher recruitment preparation should be done so through the recruitment of school can obtain a good teacher management in order to improve the quality of school-based education.